The relationship between the nursing practice environment and five nursing‐sensitive patient outcomes in acute care hospitals: A systematic review - Tamer Al‐ghraiybah; Jenny Sim; Luise Lago (Wiley, 2021)
Abstract Aim To synthesize the available evidence on the relationship between the nursing practice environment in acute care hospitals and five selected nursing‐sensitive patient outcomes (mortality, medication error, pressure injury, hospital‐acquired infection and patient fall). Design A quantitative systematic review of literature was conducted using the PRISMA reporting guidelines (PROSPERO: CRD42020143104). Methods A systematic review was undertaken up to October 2020 using: CINAHL, MEDLINE and Scopus. The review included studies exploring the relationship between the nursing practice environment in adult acute care settings and one of five selected patient outcomes using administrative data sources. Studies were published in English since 2000. Results Ten studies were included. Seven studies reported that a favourable nursing practice environment reduced the likelihood of mortality in acute care hospitals, but estimates of the effect size varied. Evidence on the association between the nursing practice environment and medication administration error, pressure injury and hospital‐acquired infection was mixed.